INFLUENCE OF SEX, AGE AND DEGREE OF ARTERIAL HYPERTENSION ON THE VASCULAR WALL STIFFNESS - Zolotaryova, N.A.; Vastyanov, R.S.; Gunenko, I.I.; Herasimenko, O.S. (World of Medicine and Biology, 2022)
The purpose of the study was to investigate the correlations between pulse wave velocity and the blood pressure degree, age and gender in patients with different degrees of arterial hypertension. 86 people were included were included into the clinical observation at the Cardiology Clinic of the Military Medical Clinical Center of the Southern Region. Patients were randomized into 2 groups – group 1 was consisted out of 71 patients with various degrees of arterial hypertension, group 2 was consisted out of 15 conditionally healthy individuals. Pulse wave velocity was measured in all patients. Authors studied in details the influence of age, gender and blood pressure level on vascular stiffness formation. The presence of a certain marker of the vascular bed functioning was shown and studied with correlative relations with the named above factors that is extremely important because one could assume the risk of a vascular catastrophe approaching according to its absolute value change. The conclusion made that age is one of the significant factors determining the vascular stiffness formation. The formation of vascular stiffness characterized also by gender characteristics. The arterial rigidity stiffness severity shown to be increased as the degree of arterial hypertension increases; it correlates with systolic blood pressure. Pulse wave velocity index determination is a sensitive marker of vascular remodeling in premorbid hypertensive conditions and in young people.
Keywords: arterial hypertension; vascular wall stiffness; rigidity; age; gender; blood pressure; pulse wave velocity